Descriptive analysis of 192 cases of breast cancer occurring before age 40 in Yaounde, Cameroon - Essiben, Félix; Foumane, Pascal; Meka, Esther JNU; Tchakounté, Michèle; Dohbit, Julius Sama; Nsahlai, Christiane; Atenguena, Etienne; Njotang, Philip Nana; Mboudou, Emile Telesphore (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Breast cancer is today a global health problem. With 1,671,149 new cases diagnosed in 2012, it is the most common female cancer in the world and accounts for 11.9% of all cancers and it affects more people than prostate cancer. In 2008, The United States statistics showed that, for all cancer that affect women before 40 years, more than 40% of them concerned the breast. The aim of this study was to describe the clinical, histopathological and therapeutic aspects of breast cancer in women under 40 years of age in Yaoundé. Methods: This was a retrospective study with data collected from 192 medical case files of women treated over a period of 12 years, from January 2004 to December 2015 at the Yaounde General Hospital and the Yaounde Gyneco-Obstetric and Pediatric Hospital. Microsoft Epi Info version 3.4.5 and SPSS version 20.0 softwares were used for data analysis. Results: From 2004 to 2015, 1489 cases of breast cancer were treated in both hospitals. Of these, 462 women were less than 40 years old, representing a proportion of 31.0%. The mean age at diagnosis was 33.5±5.0 years and 17.7% of women had a family history of breast cancer. The average time before an initial consultation was 6.7±6.6 months. Most cases were classified as T4 (46.1%). The most common histological type was ductal carcinoma (87.4%). Grades SBR II and SBR III were predominant (76.4%). Axillary dissection (64.4%) and neoadjuvant chemotherapy (43.9%) were the main therapeutic modalities. The overall survival rate at 5 years was 51.2%. Five-year survival rates with no local recurrence and no metastatic occurrence were 35.8% and 43.2% respectively. Conclusions: Breast cancer largely affects women under the age of 40 and is often discovered late, at an advanced stage. The prognosis appears poor. Only screening could facilitate diagnosis at an early stage of the disease for better outcomes.